Age dependent changes in activity of intentinal disaccharidases and alkaline phosphatase activity in CD26 deficient mice - Batičić Pučar, Lara (Array, 2008)
Summary: The profile of intestinal brush-border membrane enzyme activity is described in several mice and rat species. Dipeptidyl peptidase IV (CD26/DPP IV) is as well an intestinal brush-border membrane hydrolase. In order to examine the consequences of CD26/DPP IV deficiency on the activity of other enzymes, CD26 deficient mice were investigated. The aim of this study was to determine the influence of age on intestinal brush-border disaccharidases (lactase, sucrase, and maltase), and alkaline phosphatase activity in CD26 deficient mice. The relationship between ageing and brush-border membrane enzymes activities was characterized in different small intestinal segments (duodenum, jejunum, ileum) in mice aged 2 weeks, 1, 2, 3, 6 and 12 months. The results of this study revealed that intestinal enzyme activities change statistically significantly with ageing in CD26 deficient mice. Interestingly, the horizontal patterns (duodenum to ileum) of their activities remain not affected by age